Development of a transtheoretical model for the prevention and treatment of skin disease through ultraviolet protection based on 14,681 samples of outpatient clinics and a cross-sectional survey - Liu, Xiaoyi; Xu, Guiling; Yang, Weili; Su, Danping; Yin, Renlong; Wan, Pengjie; Deng, Dan; Xiang, Ying; Hong, Li (Frontiers in Public Health, 2025)
BackgroundLittle is known about the association between types of skin and subcutaneous diseases and UV protection literacy.ObjectiveTo assess the burden and treatment of skin diseases in Ninger County, Yunnan Province, and establish a transtheoretical model for optimizing public perceptions and behaviors regarding UV radiation.MethodsElectronic medical records of outpatients from the dermatology department were collected from January 2022 to July 2024, and a self-administered questionnaire assessed the public knowledge about UV exposure risks and behaviors. Multivariable regression models were used to investigate the correlation between UV protection literacy and dermatological situations. Knowledge, Attitude, and Practice (KAP) model was established and re-examined by Structural Equation Modeling (SEM).ResultsSignificant seasonal trends in skin disease incidence were observed. Each unit increase in UV protection knowledge score was associated with a 59.1% lower risk of pigmented skin disease and a 56.1% lower risk of skin tumors. A KAP model was developed with coefficients of 0.264 (p < 0.001), 0.603 (p = 0.041), 0.605 (p < 0.001). The impact of redundant residuals on the evaluation of the model fit cannot be ignored in SEM.ConclusionThe negative association between UV protection literacy and certain skin disease occurence revealed the essentiality of UV protection dissemination.